Use of a time-kill technique for susceptibility testing of Trichomonas vaginalis. - Krieger, J N (1985)
The emergence of metronidazole-resistant Trichomonas vaginalis and questions about the safety of metronidazole are significant concerns in treatment of trichomoniasis. At 24 h, a microtiter assay was used to test antimicrobial susceptibility of 16 recent isolates; the MICs of metronidazole ranged from less than 0.06 to 25 micrograms/ml. Observable motility as an endpoint correlated imperfectly with survival as measured in pour plates. Quantitative pour plate cultures of six T. vaginalis isolates after timed exposures to antimicrobial drugs demonstrated exquisite sensitivity to metronidazole with minimal trichomonacidal concentrations of 0.025 to 0.100 micrograms/ml. Killing of some T. vaginalis isolates by clotrimazole and rosoxacin occurred only at concentrations of 100 micrograms/ml. Resistance to both rosoxacin and clotrimazole correlated with increasing resistance to metronidazole (P less than 0.01).